Evaluation of Nanomaterials for Building Production within the Context of Sustainability - Aljenbaz, Ahmad Zeyad; Çağnan, Çiğdem (European Journal of Sustainable Development, 2020)
Nanotechnology is a new technology created by manipulating small particles in the material in order to obtain different and unique properties. It brings new solutions in economic, ecologic and social ways to participate in achieving sustainability. Nanomaterials, which are the products of this new technology, are used in building construction field with the aim of reducing the harm to the environment. The aim of this paper is to determine the effects of nanomaterials in this field. To reach the aim of the study, the topic was examined in the following sequence. Firstly, the general definition of nanotechnology and dimensional classification of nanomaterials were made. Nanotechnology, nanomaterial and nanoarchitecture applications in building production were examined together with examples. The effects of different applications were analyzed in conjunction with environmental-social and economic sustainability issues. Finally, the nanomaterials were evaluated within a test and evaluation matrix according to the environmental-social-economical sustainability criteria. Evaluation was made through the percentages of effects where (+) has positive effect, (-) has negative effect and (o) has no/unknown effect. The test results were explained in a test evaluation report. The findings of the research from the test results point out that, the use of nanomaterials in building production can help to achieve sustainability but the effects on human health have not been fully determined yet and this is the most important disadvantage of using these new tech materials. Keywords: Sustainability; nanotechnology; nanoarchitecture; nanomaterials; building production; test evaluation matrix